Sociopreneur Muda: Program Pelatihan Kewirausahaan Sosial untuk Meningkatkan Jiwa Usaha dan Kepedulian Sosial Siswa SMA Islam Andalusia Kebasen - Puspita Lianti Putri; Riska Nadiya Salsebela (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service activity aimed to introduce and strengthen the understanding of sociopreneurship among students of SMA Islam Andalusia Kebasen through an experiential learning approach. The initiative responded to the need for youth empowerment programs that combine entrepreneurial skills with social responsibility, particularly those grounded in Islamic values. The one-day training was designed to be interactive and engaging, incorporating inspirational dialogues with practitioners, interactive simulations, role-plays, and value reflections. These methods were intended to create an immersive learning experience, enabling students to connect theory with real-world application. A total of 50 students participated in the program. The training focused on three main objectives: (1) developing the ability to identify and analyze social issues in their community, (2) designing solutions through the creation of social enterprises, and (3) integrating Islamic values into business practices to ensure ethical and sustainable entrepreneurship. Evaluation was conducted using pre- and post-training assessments, observation, and participant feedback. The results indicated that 70% of participants demonstrated a strong understanding of the concept of sociopreneurship after the training. Additionally, 76% successfully integrated Islamic values into their proposed business ideas, while over 60% were able to design simple but feasible social enterprise concepts addressing real social problems. Participants also reported increased awareness, empathy, creativity, and leadership skills as outcomes of the activity. The findings highlight that experiential learning-based sociopreneurship training is an effective method for cultivating youth’s capacity to initiate social change through entrepreneurial action. This program not only enhanced students’ knowledge and skills but also inspired them to become agents of positive transformation in their communities. It is recommended that schools establish follow-up initiatives, such as sociopreneur clubs, mentoring schemes, and project incubation programs, to ensure the sustainability and further development of students’ social enterprise ideas.